Mapping the dark: a bibliometric examination of research in Dark Tourism - Alžbeta Kiráľová; Radka Šperková (Cogent Social Sciences)
This paper aimed to identify research activity on Dark Tourism based on bibliometric analysis using the WoS database with the support of the VOSviewer.The analysis revealed 10 areas where the topic of Dark Tourism was found and the top five countries with the most publications. Analysis of the level of collaboration showed the most vital link between England, Australia, and the USA. The study of keyword occurrence identified four independent thematic clusters: Dark Tourism as a tourism product, Subject of Dark Tourism, Motivation in Dark Tourism, and Emotion in Dark Tourism.The most cited authors and publications were identified as Stone and Stone and Sharpley, followed by Seaton. The network map of the co-citations identified 65 publications out of 21,295 that met the stated conditions. Three clusters were identified: the Development of Dark Tourism, the Cornerstones of Dark Tourism, and Motivations and Emotions in Dark Tourism. The top journal by the number of papers published was identified as the Journal of Heritage Tourism, and the top journal by the number of citations was identified as Tourism Management.